CRYSTAL CHEMISTRY OF FE-CONTAINING SPHALERITES - Lepetit P.; Bente K.; Doering T.; Luckhaus S. (My University, 2003)
Cell dimensions and solvus properties of Fe-containing sphalerites, depending on temperature and sulfur fugacity, were investigated using equilibrated powdered materials synthesized from elements and binary sulfides under vacuum. The Fe solvus in sphalerite, determined by optical microscopy and microprobe analysis, are directly correlated with increasing temperature and decreasing sulfur fugacity controlled by solid-state buffers. The increase of lattice parameters with Fe correlates with an increase of FeS independent of sulfur fugacity up to 10 mol% FeS within ZnS. Above about 10 mol% the lattice parameters are strongly depending on the sulfur fugacity controlled Fe3+/Fe2+ ratios. The Fe3+/Fe2+ ratios determined by Moessbauer spectroscopy and involving metal vacancies depend on the sulfur fugacity. The critical Fe2+ content determined by experimental simulations as well as the minimal Fe3+/ Fe2+ ratios agree with the required minimal Fe content for CuFeS2-DIS in sphalerite. The critical Fe2+ content also agrees with the change of Moessbauer signal from a singlet to a doublet for Fe2+ containing sphalerite. Pyrrhotite exsolutions in sphalerite caused by higher sulfur fugacity show orientationally intergrown with the sphalerite matrix. Density data calculated from lattice parameters and composition are compared with experimental density measurements.
Keywords: SPHALERITE; (ZN, FE) S SOLID SOLUTION SERIES; PYRRHOTITE EXSOLUTIONS